Meningkatan Kemampuan Berbicara Siswa melalui Storytelling pada Siswa Kelas II MI Al- Irsyad Kota Tangerang - Zuliani, Rizki; Heni, Nur; Sakina, Syera Putri (TSAQOFAH, 2023)
Speaking skill is the ability to pronounce or pronounce an idea that exists in an individual which involves several aspects of pronunciation, vocabulary, and structure. This study aims to find out that there is a problem how to describe the improvement of speaking skills through storytelling in class II students of Mi Al-Irsyad, Tangerang City. The research method used is classroom action research (PTK) with data collection techniques of observation, tests, and interviews. The main objective of PTK is to solve real problems that occur in the classroom and increase the real activities of teachers in their professional development. The results of the study showed that there was an increase in speaking skills if the average score on student test results increased, namely individual absorption of at least 70 and classically 85% of students could speak. In addition, there was also a change in students' attitudes during the learning process which was marked by the activeness of students in expressing opinions, answering questions, the level of self-confidence, the use of appropriate language when telling stories, and responsibility in the learning process.